2018
DOI: 10.3892/ol.2018.9609
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of primary thyroid leiomyosarcoma without Epstein‑Barr virus infection: A case report

Abstract: Primary thyroid leiomyosarcoma (LMS) is a rare tumor type with an unusual location, the diagnosis is based entirely on histological and immunohistochemical evaluations. In the present study, a rare case of a 74-year-old female patient who exhibited a right anterior neck mass for 12 months, which rapidly enlarged for the last 3 months. Ultrasound of the thyroid revealed a 55×42 mm hypoechoic mass with clear margins in the right lobe. Histological examination of the tumor demonstrated malignant spindle cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Primary thyroid leiomyosarcoma is an exceptionally uncommon malignancy, constituting just 0.014% of thyroid cancers [1,2]. Reported cases are sparse in the literature, often affecting elderly females, with an average age of 61.4 years [3][4][5], though Tulbah et al, [6], reported a case of a leiomyosarcoma of the thyroid in a 6-year-old child with congenital immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary thyroid leiomyosarcoma is an exceptionally uncommon malignancy, constituting just 0.014% of thyroid cancers [1,2]. Reported cases are sparse in the literature, often affecting elderly females, with an average age of 61.4 years [3][4][5], though Tulbah et al, [6], reported a case of a leiomyosarcoma of the thyroid in a 6-year-old child with congenital immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Though the pathogenesis of this tumor remains uncertain, many authors incriminate the transformation of the smooth muscle-walled vessels in the thyroid gland capsule [4][5][6][7]. Others claim that it can result of metaplasia of the smooth muscle in a thyroid anaplastic carcinoma [8], or a malignant transformation of the smooth muscles, after an Epstein-Barr virus infection [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of thyroid LMS remains unknown but may be related to smooth muscles of the vascular wall of the thyroid capsule [5]. Thyroid LMS is very rare, with only 30 cases reported worldwide [3]. The incidence of thyroid LMS is more common among the elderly, among individuals aged 40-90 years, and the male:female ratio is 1:1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Primary thyroid LMS is primarily surgically resected, including thyroidectomy and total resection with cervical lymph node dissection, and no other effective treatment currently available. Disease progression is rapid, the prognosis is poor, and the 1-year survival rate is < 10% [3]. Here, we report the case of a 76year-old woman with thyroid LMS admitted to our hospital department and a review of the literature.…”
Section: Introductionmentioning
confidence: 94%